Monuments and memorials on SADF ground: SA Intelligence School Monument and Memorial Needle - Militaria, Editorial Team (Scientia Militaria - South African Journal of Military Studies, 2012)
The SA Intelligence School has within its lines both a monument and a memorial needle. These will be individually discussed below in terms of description, history and symbolism.